Preparation method of nano ZIF-8 composite diaphragm with zinc dendritic crystal resisting function

By attaching nano ZIF-8 material to the glass fiber membrane to form a composite membrane, the problems of zinc dendrites growth and side reactions in aqueous zinc ion batteries are solved, and the cycle stability performance of the battery is significantly improved.

CN119627358APending Publication Date: 2025-03-14UNIV OF ELECTRONICS SCI & TECH OF CHINA

Patent Information

Application Number
CN202411663924.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Water-based zinc ion batteries are prone to zinc corrosion and dendrites during charging and discharging, resulting in low cycle stability and Coulomb efficiency, hindering their large-scale application.

Method used

By attaching the nano ZIF-8 material to the glass fiber membrane, a composite membrane is formed. The hydrophobicity, thermal stability and porous characteristics of ZIF-8 are used to inhibit the growth of zinc dendrites and the occurrence of side reactions.

Benefits of technology

The cycling stability performance of the zinc negative electrode is significantly improved. The battery based on this diaphragm can circulate stably for more than 2250 hours in the 2M ZnSO4 aqueous electrolyte, far exceeding the 200 hours of the unmodified diaphragm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627358A_ABST
    Figure CN119627358A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a nano ZIF-8 composite diaphragm with a zinc dendritic crystal resisting function. The diaphragm can be applied to an aqueous zinc ion battery. The preparation of the nano ZIF-8 particle composite glass fiber diaphragm can be realized through a simple one-step method under the condition of room temperature. In the composite diaphragm, the ZIF-8 is attached to the glass fiber, is in the form of a tiny granular solid, fully covers the surface of the glass fiber and is uniformly distributed. The process is simple, the preparation speed is high, and the green chemical requirement is met. Compared with a common glass fiber diaphragm, the obtained ZIF-8 modified glass fiber diaphragm has obviously improved cycle stability in a symmetric battery. Under the current density of 1mA cm <-2 >, the button-type symmetrical battery additionally provided with the modified diaphragm can stably circulate for more than 2250 hours in a ZnSO4 aqueous electrolyte, and the button-type symmetrical battery additionally provided with the unmodified glass fiber diaphragm can only stably circulate for less than 200 hours under the same condition. The diaphragm shows excellent cycle stability, and is an aqueous zinc ion battery diaphragm material with application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemical technology, and specifically relates to a preparation method and application of a nano ZIF-8 composite diaphragm with anti-zinc dendrite function, which can be used as an anti-zinc dendrite high-performance aqueous zinc ion battery diaphragm. Background Art

[0002] Modification is a widely used technology, which is characterized by the ability to selectively enhance certain advantages of the modified material or give it new properties. The general principle of modification is to further affect the chemical and electrochemical properties of the material by changing its surface characteristics, thereby obtaining a new material that has the advantages of both the modified material and the modified material. However, when applying modification, the antagonism of material properties may occur, resulting in a decrease in performance in some aspects. It is relatively difficult to select materials suitable for modification. The selection process requires a lot of experimental verification, and new materials with superior comprehensive performance or required specific performance are sought in the experiment.

[0003] Aqueous zinc-ion batteries have become one of the candidates for next-generation energy storage devices due to their high safety and environmental friendliness. 2+ The standard electrode potential of Zn is lower than that of H + / H2 standard electrode potential, zinc corrosion will inevitably occur during the charge and discharge process. The instability of the zinc negative electrode (i.e., the formation of surface dendrites and hydrogen evolution reaction leading to low coulombic efficiency and poor cycle stability) seriously hinders the large-scale application of zinc ion batteries. Therefore, how to inhibit the dendrite growth problem of the zinc negative electrode and reduce the occurrence of side reactions is the key to improving the cycle life of aqueous zinc ion batteries. Some studies have shown that optimizing the diaphragm can greatly improve the cycle performance of aqueous zinc ion batteries, such as by regulating the zinc ion flux, promoting the uniform distribution of zinc ions on the electrode surface, and limiting the migration of active water molecules, thereby inhibiting the growth of zinc dendrites and the occurrence of side reactions such as hydrogen evolution and oxygen absorption. Here, we apply the idea of ​​modification and modification to the performance optimization of the diaphragm, taking advantage of the rich and regular pores, hydrophobicity and good thermal stability of ZIF-8 materials, and attaching ZIF-8 materials to the surface of the glass fiber diaphragm to enhance the selectivity of the diaphragm, inhibit the side reactions, and improve the battery cycle performance. Summary of the invention

[0004] In view of the above existing technical problems, the present invention provides a nano ZIF-8 (full name: Zeolitic Imidazolate Framework-8; English full name: Zeolitic Imidazolate Framework-8; its molecular formula is: C8H 12The invention discloses a composite glass fiber diaphragm modified with N4·Zn and its preparation method and application. The preparation method has a simple process, a relatively fast preparation speed and meets the requirements of green chemistry. The obtained diaphragm exhibits excellent cycle stability and is a water-based zinc ion battery diaphragm material with application prospects.

[0005] The technical solution adopted by the present invention for the above technical problem is: a method for preparing a nano ZIF-8 composite diaphragm with anti-zinc dendrite function, the method comprising:

[0006] Step 1: Dissolve zinc nitrate hexahydrate in ethanol, add ethanolamine dropwise and stir to prepare a sol, and let stand;

[0007] Step 2: Dissolve 2-methylimidazole in ethanol, pour into the sol prepared in step 1, and mix and stir;

[0008] Step 3: Repeat centrifugal washing and ultrasonic dispersion of the mixture obtained in step 2, dry it in a vacuum oven, and grind it to obtain ZIF-8 powder;

[0009] Step 4: The ZIF-8 powder obtained in step 3 is prepared into a colloidal solution, and the GF / D membrane is immersed in the solution for modification. After uniform adsorption, the solution is taken out and placed in an oven for drying to obtain a ZIF-8 modified glass fiber membrane; the GF / D membrane is a glass fiber membrane.

[0010] Furthermore, the volume fraction ratio of ethanol to ethanolamine used in step 1 is 2-20%, the stirring time is 10-90 minutes, and the standing time is 20-25 hours;

[0011] Furthermore, the concentration of 2-methylimidazole and ethanol in step 2 is 1 to 10 g mL -1 , mixing and stirring time is 1 to 3 hours;

[0012] Furthermore, in the colloidal solution obtained in step 4, the concentration of ZIF-8 solution is 10 to 100 mg L -1 The dispersant is a mixture of water and ethanol, and a uniform ZIF-8 particle colloidal solution is formed by ultrasonic dispersion, wherein the volume fraction of ethanol accounts for 10 to 50%.

[0013] Furthermore, the prepared composite membrane nano ZIF-8 has a unit area loading of 1-5 mg cm -2 .

[0014] Furthermore, the ZIF-8 modified glass fiber membrane prepared in step 4 is used as an aqueous zinc ion battery membrane.

[0015] The beneficial effects of the present invention are as follows: the present invention uses the membrane composite technology to attach ZIF-8 to the glass fiber membrane to form a particle layer, which has the characteristics of hydrophobicity, good thermal stability and porosity, can induce uniform zinc deposition and reduce the generation of zinc dendrites, while inhibiting the occurrence of side reactions, thereby improving the cycle stability of the zinc negative electrode. -2 At a current density of , the button-type symmetrical battery based on the membrane can stably cycle for more than 2250 hours in a 2M ZnSO4 aqueous electrolyte, while the button-type symmetrical battery based on the unmodified membrane can only stably cycle for less than 200 hours under the same conditions. The present invention has a simple process, fast preparation speed and meets the requirements of green chemistry, demonstrating a glass fiber membrane with excellent cycle stability and its application in aqueous zinc ion battery membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The X-ray diffraction and scanning electron microscope images of the ZIF-8 powder synthesized in Example 1 of the present invention;

[0017] Figure 2 This is a scanning electron microscope image of the original glass fiber diaphragm in Example 1 of the present invention;

[0018] Figure 3 The optical photograph and scanning electron microscope image of the nano ZIF-8 composite membrane in Example 1 of the present invention;

[0019] Figure 4 Element distribution diagram of the nano ZIF-8 composite diaphragm in Example 1 of the present invention;

[0020] Figure 5 This is an X-ray diffraction test diagram of the nano ZIF-8 composite diaphragm in Example 1 of the present invention;

[0021] Figure 6 The cyclic stability performance comparison of the button-type symmetrical battery based on the nano ZIF-8 composite membrane and the button-type symmetrical battery based on the unmodified membrane in Example 1 of the present invention in 2M ZnSO4 aqueous electrolyte respectively;

[0022] Figure 7 The SEM images of the zinc sheet electrodes of the button-type symmetrical cells based on the nano ZIF-8 composite membrane and the unmodified membrane in Example 1 of the present invention after cycle testing in 2M ZnSO4 aqueous electrolyte respectively;

[0023] Figure 8 The XRD test diagram of the zinc sheet electrode of the button-type symmetrical battery based on the ZIF-8-GF / D membrane and the unmodified membrane in Example 1 of the present invention after cycle testing in a 2M ZnSO4 aqueous electrolyte;

[0024] Fig. 9This is a scanning electron microscope and element distribution diagram of the zinc negative electrode using the nano ZIF-8 composite membrane after cycling in Example 1 of the present invention.

[0025] Specific example method

[0026] A ZIF-8 modified glass fiber diaphragm, which is a granular ZIF-8 solid loaded on the surface of the glass fiber, the particle layer is composed of nano-scale ZIF-8 particles, has hydrophobicity and good thermal stability, and is evenly distributed on the surface of the glass fiber. Modification and modification technology can further change the chemical and electrochemical properties of the material by changing the surface characteristics of the material, and obtain a new material with the advantages of both the modifying material and the modified material. Using this principle, ZIF-8 powder is prepared according to the ZIF-8 preparation strategy. Under room temperature conditions, the glass fiber diaphragm is soaked in an appropriate concentration of ZIF-8 ethanol solution for a period of time and then taken out and dried, so that ZIF-8 modification of the glass fiber diaphragm can be achieved, and finally a ZIF-8 modified glass fiber diaphragm is obtained. Granular ZIF-8 solid is loaded on the surface of the glass fiber, the particle layer is composed of nano-scale ZIF-8 particles, has hydrophobicity, good thermal stability and porous characteristics, and is evenly distributed on the surface of the glass fiber. The particle layer can induce uniform zinc deposition and reduce the generation of zinc dendrites, while inhibiting the occurrence of side reactions, thereby improving the cycle stability of the diaphragm. Therefore, the diaphragm is a promising aqueous zinc-ion battery diaphragm material.

[0027] Example 1

[0028] A preparation method and application of a nano ZIF-8 composite diaphragm with anti-zinc dendrite function includes:

[0029] 1) Weigh 2.98g zinc nitrate hexahydrate and dissolve it in 200ml ethanol, add 4ml ethanolamine and stir for 1h to prepare sol, let it stand for 23h, weigh 6.56g 2-methylimidazole and dissolve it in 200ml ethanol, pour it into the prepared sol and stir for 2h. The obtained mixture is centrifuged and washed 3 times and ultrasonically dispersed, placed in a vacuum oven at 60℃ and dried, and then ground to obtain ZIF-8 powder.

[0030] 2) The ZIF-8 powder obtained in step 1) was dispersed in a mixed solvent of 90% ethanol to prepare a 60 mg / L -1 The GF / D membrane with a diameter of 16 mm was modified by immersing it in 5 mL of the solution for 5 s. The membrane was taken out and dried in an oven at 60 °C to obtain a ZIF-8 composite glass fiber membrane.

[0031] Taking the nano ZIF-8 composite membrane in this embodiment as an example, the XRD detection comparison results of the pure phase ZIF-8 powder prepared by the present invention are shown in the attached Figure 1 As shown, the morphology is nanoscale ZIF-8 particles. Figure 2 and Figure 3 The following are the SEM images of the glass fiber membrane before and after immersion modification. It can be seen that the surface of the glass fiber is smooth at the beginning, and no obvious protrusions can be seen; after the ZIF-8 is attached, obvious granular solids appear on the surface of the glass fiber, and the size is about nanometers. The element distribution test of the glass fiber membrane found that the main elements of the attached solids are C, N, Zn ( Figure 4 ), which is the main element of ZIF-8, indicating that the nano ZIF-8 particles are successfully attached to the surface of glass fiber. Figure 5 As shown, the ZIF-8 modified glass fiber membrane was further subjected to X-ray diffraction analysis and testing, and it was found that the characteristic broad peak of the glass fiber and the characteristic diffraction peak of ZIF-8 appeared in the nanocomposite membrane at the same time, and no other impurity peaks appeared, proving that the nano ZIF-8 composite membrane was successfully synthesized in this experiment.

[0032] like Figure 6 As shown in the figure, when the ZIF-8 modified glass fiber separator prepared in this example is used as the separator of button-type symmetrical battery, the -2 At a current density of , the button-type symmetrical battery based on the nano ZIF-8 composite membrane can stably cycle for more than 2250 hours in a 2M ZnSO4 aqueous electrolyte; while for the unmodified membrane, it can only stably cycle for less than 200 hours under the same test conditions. Furthermore, the morphology of the electrode surface after the cycle test was analyzed. Figure 7 As shown, ZIF-8-GF / D membrane has a -2 After cycling for 2250 hours under the conditions of , the zinc deposition on the zinc electrode surface of the symmetrical battery is very uniform, the zinc flakes deposited on the electrode surface are very small, and the distribution of the zinc flakes is regular and orderly, which has almost no impact on the diaphragm. However, the zinc deposition on the zinc electrode surface of the symmetrical battery assembled with the unmodified original diaphragm is very uneven, and grows in irregular block stacks. The zinc flakes deposited on the electrode surface are larger in size and have a higher probability of piercing the diaphragm. The surface of the zinc flake electrode of the button cell after cycling was further analyzed by X-ray diffraction. Figure 8 As shown in the figure, the surface impurity peaks of the symmetric battery of the ZIF-8 modified glass fiber separator are significantly less than that of the original separator, which can prove that the modification of the glass fiber separator by ZIF-8 has a significant effect in inhibiting the generation of side reactants near the zinc electrode. Fig. 9 As shown in the figure, the scanning electron microscope image and corresponding elemental analysis after cycling show that the deposited product on the surface of the zinc negative electrode is mainly zinc, with a small amount of impurity elements. Therefore, the ZIF-8 modified glass fiber separator exhibits excellent cycle stability and is a promising aqueous zinc ion battery separator material.

[0033] Example 2

[0034] A preparation method and application of a nano ZIF-8 composite diaphragm with anti-zinc dendrite function includes:

[0035] 1) Weigh 1.49 g zinc nitrate hexahydrate and dissolve it in 100 mL ethylene glycol, add 2 mL ethanolamine and stir for 30 min to prepare a sol, let it stand for 22 h, weigh 3.28 g 2-methylimidazole and dissolve it in 100 mL methanol, pour it into the prepared sol and stir for 2 h. The obtained mixture is centrifuged and washed twice and ultrasonically dispersed, placed in a vacuum oven at 50 ° C, and then ground to obtain ZIF-8 powder.

[0036] 2) The ZIF-8 powder obtained in step 1) was dispersed in a mixed solvent of 50% ethylene glycol to prepare a 60 mg L -1 colloidal solution, prepared as 80 mg mL -1 The GF / D membrane with a diameter of 12 mm was immersed in 4 mL of the solution for 4 s for modification, and then taken out and dried in an oven at 60 °C to obtain a ZIF-8 composite glass fiber membrane.

[0037] Taking the ZIF-8 composite glass fiber separator obtained in this embodiment as an example, the cycle stability performance improvement effect based on the symmetrical battery tested in 2M ZnSO4 is similar to that in Example 1.

[0038] Example 3

[0039] A preparation method and application of a nano ZIF-8 composite diaphragm with anti-zinc dendrite function includes:

[0040] 1) Weigh 2.98g zinc chloride hexahydrate and dissolve it in 150mL propanol, add 4mL ethanolamine and stir for 1h to prepare a sol, let it stand for 24h, weigh 6.56g 2-methylimidazole and dissolve it in 150mL propanol, pour it into the prepared sol and stir for 2h. The obtained mixture is centrifuged and washed 4 times and ultrasonically dispersed, placed in a vacuum oven at 60°C for drying, and then ground to obtain ZIF-8 powder.

[0041] 2) The ZIF-8 powder obtained in step 1) was dispersed in a mixed solvent of 80% propanol to prepare 80 mg L -1 A glass fiber membrane with a diameter of 14 mm was modified by immersing it in 7 mL of the solution for 5 seconds, and then taken out and dried in an oven at 60°C to obtain a ZIF-8 composite glass fiber membrane.

[0042] Taking the ZIF-8 composite glass fiber separator obtained in this embodiment as an example, the cycle stability performance improvement effect based on the symmetrical battery tested in 2M ZnSO4 is similar to that in Example 1.

[0043] Example 4

[0044] A preparation method and application of a nano ZIF-8 composite diaphragm with anti-zinc dendrite function includes:

[0045] 1) Weigh 2.98g zinc nitrate hexahydrate and dissolve it in 200mL methanol, add 3ml ethanolamine and stir for 90min to prepare sol, let it stand for 23h, weigh 6.56g 2-methylimidazole and dissolve it in 200mL methanol, pour it into the prepared sol and stir for 3h. The obtained mixture is centrifuged and ultrasonically dispersed for 3 times, dried in a vacuum oven at 70℃, and then ground to obtain ZIF-8 powder.

[0046] 2) The ZIF-8 powder obtained in step 1) was dispersed in a mixed solvent of 80% methanol to prepare 60 mg L -1 The GF / D membrane with a diameter of 16 mm was modified by immersing it in 5 mL of the solution for 5 s. The membrane was taken out and dried in an oven at 70 °C to obtain a ZIF-8 composite glass fiber membrane.

[0047] Taking the ZIF-8 composite glass fiber separator obtained in this embodiment as an example, the cycle stability performance improvement effect based on the symmetrical battery tested in 2M ZnSO4 is similar to that in Example 1.

[0048] Example 5

[0049] A preparation method and application of a nano ZIF-8 composite diaphragm with anti-zinc dendrite function includes:

[0050] 1) Weigh 1.49 g zinc nitrate hexahydrate and dissolve it in 100 ml isopropanol, add 4 ml ethanolamine and stir for 1 hour to prepare a sol, let it stand for 22 hours, weigh 3.3 g 2-methylimidazole and dissolve it in 300 ml isopropanol, pour it into the prepared sol and stir for 1 hour. The obtained mixture is centrifuged and washed twice and ultrasonically dispersed, placed in a vacuum oven at 60°C for drying, and then ground to obtain ZIF-8 powder.

[0051] 2) The ZIF-8 powder obtained in step 1) was dispersed in a mixed solvent of 50% isopropanol to prepare a 30 mg L -1 The GF / D membrane with a diameter of 16 mm was modified by immersing it in 6 mL of the solution for 5 s. The membrane was taken out and dried in an oven at 60 °C to obtain a ZIF-8 composite glass fiber membrane.

[0052] Taking the ZIF-8 composite glass fiber separator obtained in this embodiment as an example, the cycle stability performance improvement effect based on the symmetrical battery tested in 2M ZnSO4 is similar to that in Example 1.

[0053] Example 6

[0054] A preparation method and application of a nano ZIF-8 composite diaphragm with anti-zinc dendrite function includes:

[0055] 1) Weigh 4.47 g zinc sulfate hexahydrate and dissolve it in 300 mL methanol, add 6 ml ethanolamine and stir for 90 min to prepare a sol, let it stand for 24 h, weigh 9.84 g 2-methylimidazole and dissolve it in 300 mL ethanol, pour it into the prepared sol and mix and stir for 3 h. The obtained mixture is centrifuged and washed 5 times and ultrasonically dispersed, placed in a vacuum oven at 60 ° C, and then ground to obtain ZIF-8 powder.

[0056] 2) The ZIF-8 powder obtained in step 1) was dispersed in a mixed solvent of 50% isopropanol to prepare 100 mg L -1 The glass fiber diaphragm with a diameter of 16 mm was immersed in 3 mL of the solution for 5 s for modification, and then taken out and dried in an oven at 70 °C to obtain a ZIF-8 composite glass fiber diaphragm.

[0057] Taking the ZIF-8 composite glass fiber separator obtained in this embodiment as an example, the cycle stability performance improvement effect based on the symmetrical battery tested in 2M ZnSO4 is similar to that in Example 1.

[0058] Although implementation cases have been listed and described in detail here, those skilled in the art will appreciate that various improvements, additions, substitutions, etc. may be made without departing from the core content of the present invention, and these contents are considered to be within the scope of the present invention as defined by the claims.

Claims

1. A method for preparing a nano ZIF-8 composite diaphragm with anti-zinc dendrite function, the method comprising: Step 1: Dissolve zinc nitrate hexahydrate in ethanol, add ethanolamine dropwise and stir to prepare a sol, and let stand; Step 2: Dissolve 2-methylimidazole in ethanol, pour into the sol prepared in step 1, and mix and stir; Step 3: Repeat centrifugal washing and ultrasonic dispersion of the mixture obtained in step 2, dry it in a vacuum oven, and grind it to obtain ZIF-8 powder; Step 4: The ZIF-8 powder obtained in step 3 is prepared into a colloidal solution, and the GF / D membrane is immersed in the solution for modification. After uniform adsorption, the solution is taken out and placed in an oven for drying to obtain a ZIF-8 modified glass fiber membrane; the GF / D membrane is a glass fiber membrane.

2. The method for preparing a nano ZIF-8 composite diaphragm with anti-zinc dendrite function according to claim 1, characterized in that: The volume fraction ratio of ethanol to ethanolamine used in step 1 is 2-20%, the stirring time is 10-90 minutes, and the standing time is 20-25 hours.

3. The method for preparing a nano ZIF-8 composite diaphragm with anti-zinc dendrite function according to claim 1, characterized in that: The concentration of 2-methylimidazole and ethanol in step 2 is 1-10 g mL -1 , the mixing and stirring time is 1 to 3 hours.

4. The method for preparing a nano ZIF-8 composite diaphragm with anti-zinc dendrite function according to claim 1, characterized in that: In the colloidal solution prepared in step 4, the concentration of ZIF-8 solution is 10-100 mg L -1 The dispersant is a mixture of water and ethanol, and a uniform ZIF-8 particle colloidal solution is formed by ultrasonic dispersion, wherein the volume fraction of ethanol accounts for 10 to 50%.

5. The method for preparing a nano ZIF-8 composite diaphragm with anti-zinc dendrite function according to claim 1, characterized in that: The unit area loading of nano ZIF-8 in the prepared composite membrane is 1-5 mg cm -2 .

6. The method for preparing a nano ZIF-8 composite diaphragm with anti-zinc dendrite function according to claim 1, characterized in that: The ZIF-8 modified glass fiber membrane prepared in step 4 is used as an aqueous zinc ion battery membrane.

Citation Information

Patent Citations

  • Zinc ion battery and method for improving cycle performance of zinc negative electrode of zinc ion battery

    CN114142032A

  • Zinc ion battery diaphragm prepared by grafting treatment technology and application thereof

    CN115863910A

  • Electronic device and operation method of electronic device for arranging object according to space in augmented reality(AR)

    KR1020240019671A

Cited By

  • Zinc negative electrode-diaphragm integrated structure containing dynamic self-adaptive protection and preparation method of zinc negative electrode-diaphragm integrated structure

    CN122118126A